2009
DOI: 10.3382/ps.2008-00287
|View full text |Cite
|
Sign up to set email alerts
|

Crating and heat stress influence blood parameters and heat shock protein 70 expression in broiler chickens showing short or long tonic immobility reactions

Abstract: Two hundred thirty-five 1-d-old broiler chickens showing short or long tonic immobility responses were classified as low fear (LF) or high fear (HF) responders, respectively. On d 41, they were subjected to either crating or heat challenge (34 +/- 1 degrees C) for 3 h and its effect on plasma corticosterone concentration, heterophil/lymphocyte ratios, and heat shock protein (HSP) 70 expression in brain tissue were determined. Crating and heat exposure elevated heterophil/lymphocyte ratios in both LF and HF bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
50
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(62 citation statements)
references
References 35 publications
8
50
0
4
Order By: Relevance
“…In the present study, the thermal treatment during late embryonic development had a numerical effect on the serum level of Cort at hatch, while the level of Cort was significantly higher in the TCH group as compared to the control. Our results are in agreement with Zulkifli et al (2009) and Vishwajit et al (2012) who reported that heat challenge may elevate Cort in broiler chickens. These results suggest that the application of TM at 38.5°C in late embryonic development succeeded in reducing the negative effect of heat stress in those chicks during early exposure to stressful environmental conditions.…”
Section: Discussionsupporting
confidence: 83%
“…In the present study, the thermal treatment during late embryonic development had a numerical effect on the serum level of Cort at hatch, while the level of Cort was significantly higher in the TCH group as compared to the control. Our results are in agreement with Zulkifli et al (2009) and Vishwajit et al (2012) who reported that heat challenge may elevate Cort in broiler chickens. These results suggest that the application of TM at 38.5°C in late embryonic development succeeded in reducing the negative effect of heat stress in those chicks during early exposure to stressful environmental conditions.…”
Section: Discussionsupporting
confidence: 83%
“…There is a question of whether the hsp 70 reaction to transportation is attributed to thermal stress per se or in combination with other noxious stimuli such as noise, acceleration and feed and water deprivation. Zulkifli et al (2009) reported that chickens subjected to crating and left stationary in a room with an ambient temperature of 248C showed an increase in hsp 70 expressions. Thus, the hsp 70 response noted in this study could be attributed to the additive effects of various stressors associated with road transportation.…”
Section: Discussionmentioning
confidence: 99%
“…There are some reports that heat challenge may elevate corticosterone in broiler chickens (Edens and Siegel, 1975;Zulkifli et al, 1999Zulkifli et al, , 2003Zulkifli et al, , 2009Mahmoud et al, 2004). However, Lin et al (2006) and Han et al (2010) reported that HT did not affect plasma corticosterone concentrations.…”
Section: Discussionmentioning
confidence: 90%